2012
DOI: 10.1002/j.1875-9114.2012.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pharmacist‐Managed Hypertension Program on Health System Costs: An Evaluation of the Study of Cardiovascular Risk Intervention by Pharmacists—Hypertension (SCRIPHTN)

Abstract: Our model found that community pharmacist interventions capable of reducing systolic blood pressure by 5.6 mm Hg within 6 months are cost saving and result in improved patient outcomes. Wider adoption of pharmacist-managed hypertension care for patients with diabetes and hypertension is encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 31 publications
0
58
0
2
Order By: Relevance
“…18,19 The identification and resolution of drug therapy problems increase the consumption of some health care services and drugs. [14][15][16] For example, in the present study, several patients had elevated LDL cholesterol levels when considering their 10-year risk score for coronary heart disease, but these patients were not using a statin at baseline. Every patient who was enrolled in the pharmaceutical care group and presented elevated LDL cholesterol levels initiated the use of statins during the study, whereas many patients who were enrolled in the usual care group did not start the use of statins.…”
Section: Economic Evaluation Of a Pharmaceutical Care Program For Eldmentioning
confidence: 62%
See 2 more Smart Citations
“…18,19 The identification and resolution of drug therapy problems increase the consumption of some health care services and drugs. [14][15][16] For example, in the present study, several patients had elevated LDL cholesterol levels when considering their 10-year risk score for coronary heart disease, but these patients were not using a statin at baseline. Every patient who was enrolled in the pharmaceutical care group and presented elevated LDL cholesterol levels initiated the use of statins during the study, whereas many patients who were enrolled in the usual care group did not start the use of statins.…”
Section: Economic Evaluation Of a Pharmaceutical Care Program For Eldmentioning
confidence: 62%
“…[14][15][16][17] Previous studies have verified that pharmaceutical care is useful for achieving adequate disease control for diabetes mellitus and hypertension in elderly patients. [18][19][20][21][22] However, to the authors' knowledge, most of the published studies have focused on the clinical outcomes of pharmaceutical care, and few studies have reported the economic cost and cost-effectiveness of pharmaceutical care.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Initially medical colleagues raised concerns about pharmacists taking on prescribing responsibilities due to pharmacists' limited diagnostic skills however these issues appear to have resolved over time and many PIPs are now integrated into the multidisciplinary team. 12 While most published literature on pharmacist prescribing describes primary care management of chronic conditions such as hypertension and secondary prevention in stroke, 13,14 there is potential to impact patient care and safety in hospital settings.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth asking the question about the cost-effectiveness of pharmaceutical care. The estimates of Houle et al [24] are interesting: they estimated the profit per patient at $131 Canadian for a six-month programme, and $115 for the annual programme of pharmaceutical care. Financial benefits were also evident when, after six months of cessation of further pharmaceutical care and over time, the impact of pharmaceutical services on the value of the blood pressure should be considered doubtful (Fig.…”
Section: The Role Of the Pharmacist In The Treatment Of Cvdmentioning
confidence: 99%